The Application Management of the Students' Achievement - Eka Wahyu Soleha; Wan Yuliyanti; Herpendi Herpendi (INFOKUM, 2022)
Politala have many prestigious achievements have been achieved. In 2019 Politala won the Best Polytechnic Vocational Band award in Indonesia. Most recently in 2022 one of the students won the title of Favorite Champion in the International Program of Management and Business competition. Politala supports student achievement, both in the academic and non-academic fields, because this achievement is one of the important points of assessment by assessors during accreditation. Apart from that, it also indirectly becomes a promotional medium for Politala for prospective new students who want to join. Student achievements cannot be obtained instantly, but there must be data collection and coaching by the institution. So far, data collection has been carried out by departments and has not been well documented. The development of technology in the field of software today can be a Politala solution in managing student achievement and talent based on applications to facilitate archiving and data security so that it becomes effective and efficient. This study aims to develop a website-based application to facilitate student affairs in the department in managing students' interests, talents and academic and non-academic achievements. The managed data can be accessed by the Deputy Director for Student Affairs for the purposes of coaching, one of which is. For majors, the data that has been collected can be easily accessed for the purposes of document evidence for accreditation. This research was conducted with the Prototype method. Model design with DFD and ERD. Programming languages ​​use PHP, HTML and Javascript.